Seasonal, spatial, and maternal effects on gut microbiome in wild red squirrels - Ren, Tiantian; Boutin, Stan; Humphries, Murray M.; Dantzer, Ben; Gorrell, Jamieson C.; Coltman, David W.; McAdam, Andrew G.; Wu, Martin (BioMed Central, 2017)
Our understanding of gut microbiota has been limited primarily to findings from human and laboratory animals, but what shapes the gut microbiota in nature remains largely unknown. To fill this gap, we conducted a comprehensive study of gut microbiota of a well-studied North American red squirrel (Tamiasciurus hudsonicus) population. Red squirrels are territorial, solitary, and live in a highly seasonal environment and therefore represent a very attractive system to study factors that drive the temporal and spatial dynamics of gut microbiota. https://viurrspace.ca/bitstream/handle/10613/5417/Gorrell.Microbiome.pdf?sequence=4 This is an electronic version of an article that was published as: Ren, T., Boutin, S., Humphries, M.M., Dantzer, B., Gorrell, J.C., Coltman, D.W., McAdam, A.G., & Wu, M. (2017). Seasonal, spatial, and maternal effects on gut microbiome in wild red squirrels. Microbiome, 5, 1-14. DOI:10.1186/s40168- 017-0382-3 Microbiome is an open access journal published by BioMed Central. More information about the journal can be found at: https://microbiomejournal.biomedcentral.com/. This article can be accessed at: http://dx.doi.org/10.1186/s40168-017-0382-3. Article 163